Ultrasound-assisted synthesis of pyrazolo[3,4-b]pyridines as potential corrosion inhibitors for mild steel in 1.0 M HCl - Dandia A.; Gupta S.L.; Singh P.; Quraishi M.A. (My University, 2025)
Five synthesized pyrazolopyridine derivatives, such as 4-(2-chloro-6- flurpphenyl)-3-methyl-6-oxo-4,5,6,7-tetrahydro-2H-pyrazolo[3,4-b] pyridine-5-carbonitrile (AP-1), 3-methyl-6-oxo-4,5,6,7-tetrahydro-2H-pyrazolo[3, 4-b]pyridine-5-carbonitrile (AP-2), 3-methyl-6-oxo-4-(p-tolyl)-4,5,6,7- tetrahydro-2H-pyrazolo[3,4-b]pyridine-5-carbonitrile (AP-3), 4-(4-methoxyphenyl)-3-methyl-6-oxo-4,5,6,7-tetrahydro-2H-pyrazolo[3,4-b] pyridine-5-carbonitrile (AP-4), and 3-methyl-6-oxo-4-(3,4,5-trimethoxyphenyl)-4, 5,6,7-tetrahydro-2H-pyrazolo[3,4-b]pyridine-5-carbonitrile (AP-5) have been synthesized using ultrasonic irradiation in aqueous medium using p-TSA as a catalyst, and their effect on corrosion of mild steel (MS) in 1.0 M HCl has been investigated using different experimental techniques like weight loss, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization techniques. The potentiodynamic polarization data indicated that the pyrazolo[3,4-b]pyridine derivatives behaved as a mixed type. The cathodic effect was more pronounced and AP-5 showed best inhibiting performance giving inhibition efficiency of 95.2% at 100 ppm. The adsorption of studied compounds obeyed the Langmuir adsorption isotherm. © 2013 American Chemical Society.